John Rechy: Bodies and Souls and the Homoeroticization of the Urban Quest - David William Foster (Studies in 20th & 21st Century Literature, 2001)
It has been difficult for John Rechy to become established in the canon of Chicano literature, in large part because of the homophobia that held sway during the formative period of Chicano literary criticism. However, now recognized as a founding figure of U.S. homoerotic writing, Rechy is also widely recognized as important to the Chicano literary tradition. This study focuses on the importance of Rechy less as a gay writer than to explore the ways in which his great Los Angeles novel, Bodies and Souls (1983), explores the conflicts between sexuality and the emotionally and physically deadening effects of modern urban society. Homoerotic desire, as much as erotic desire in general, emerges as a project of impossible fulfillment in the sex-dead Los Angeles that is an icon of the American landscape.
Keywords: John Rechy; Chicano literature; Chicano/a; homophobia; U.S. homoerotic writing; homoeroticism; homoerotic writing; sexuality; urban society; erotic desire; homoerotic desire; homosexuality